2020
DOI: 10.37441/cejer/2020/2/2/7918
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Work and Job Satisfaction among Romanian Lower Secondary Teachers

Abstract: The purpose of this paper is to provide an empirical based understanding of the Romanian context of teacher work, which provides an opportunity to identify characteristics considered to affect teaching activities and gives a basis for planning and conducting other research on teachers working conditions. The paper is based on authors' research which is a secondary analysis of Teaching and Learning International Survey (TALIS) 2013 database. The database contains the survey responses of teachers of lower second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Findings are consistent with the results of the studies undertaken by WHO [36], indicating that people involved and engaged in sports and physical activities are more resilient and can cope with stressors and negative emotions such as anxiety and aggression from their environments. The same nding was also reported by Zoller and Bacskai [92], who stated that there is a statistically signi cant positive relationship between one's involvement in physical activities and their psychological well-being. Some other studies also con rmed the signi cant contribution of physical activities to people's mental health.…”
Section: Effects Of Teachers' Physical Activities On Their Mental Hea...supporting
confidence: 83%
“…Findings are consistent with the results of the studies undertaken by WHO [36], indicating that people involved and engaged in sports and physical activities are more resilient and can cope with stressors and negative emotions such as anxiety and aggression from their environments. The same nding was also reported by Zoller and Bacskai [92], who stated that there is a statistically signi cant positive relationship between one's involvement in physical activities and their psychological well-being. Some other studies also con rmed the signi cant contribution of physical activities to people's mental health.…”
Section: Effects Of Teachers' Physical Activities On Their Mental Hea...supporting
confidence: 83%
“…Zoller and Bacskai analyze fundamental aspects of job satisfaction in the Romanian educational system, namely, job satisfaction, self-efficacy, and school climate, concluding that job satisfaction, in Romanian lower secondary education, is dependent on professional development, a disciplined atmosphere, teacher–student relationships, and stakeholder relations [ 7 ]. Despite various issues, teachers’ job satisfaction and well-being depend on relationships; therefore, policy makers might consider the impact of their implemented policies on school climates.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy and collegiality need to be assessed in a balanced way, because they have certain forms, which coupled with workplace conditions seem to have a higher positive influence on the professional development of teachers. Collaboration is part of the teaching profession; therefore, efficient collaboration with colleagues [ 7 ] increases well-being and has beneficial effects on the classroom environment, as Yang et al [ 84 ] pointed out. Zoller et al [ 7 ] observed that teachers have an internal desire to learn and develop professionally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary education has a prospective character and is the main tool to facilitate access to information, to transmit the products of human thought, with the status of knowledge that a community has accumulated. In the contemporary social context, when information and knowledge are the main factors of development, it is expected that the education system will make a prospective development effort and assign to the school the role of knowledge and responsibility for the normal development of society (Zoller & Bacskai, 2020).…”
Section: Introductionmentioning
confidence: 99%